Midwifery management of second-degree perineal tears in New Zealand: A cross-sectional survey of practice. Issue 5 (October 2018) - Cronin, Robin S.; Li, Minglan; Culliney, Kate; Maude, Robyn; Nelson, Katherine
Abstract: Background: Second-degree tears are the most common form of perineal trauma occurring after vaginal birth managed by New Zealand midwives, although little is known about midwives' perineal practice. Aim: The aim of this study was to identify how midwives managed the last second-degree perineal tear they treated and the level to which their practice reflects National Institute for Health and Care Excellence guidelines. Methods: An (anonymous) online survey was conducted over a six-week period in 2013. New Zealand midwives who self-identified as currently practising perineal management and could recall management of the last second-degree tear they treated were included in the analysis. Findings: Of those invited, 645 (57.1% self-employed, 42.9% employed) were eligible and completed surveys. Self-employed midwives reported greater confidence (88.0% vs 74.4%, p < 0.001) and more recent experience (85.1% vs 57.4%, p < 0.001) with perineal repair than employed midwives. Midwives who left the last second-degree tear unsutured (7.3%) were more likely to report low confidence (48.9% vs 15.4%, p < 0.001) and less recent experience with repair (53.2% vs 24.7%, p < 0.001), and were less likely to report a digital-rectal examination (10.6% vs 49.0%, p < 0.001), compared to midwives who sutured. Care consistent with evidence-based guidelines (performing a digital-rectal examination, 59.4% vs 49.3% p = 0.005; optimal suturing techniques, 62.2% vs 48.7%, p = 0.001) was associated with recent perineal education. Conclusions: Midwives' management of the last second-degree perineal tear is variable and influenced by factors including: employment status, experience, confidence, and perineal education. There is potential for improvement in midwives' management through increased uptake of evidence-based guidelines and through ongoing education.